Study of ambient radiation exposure in Bagmati Province, Nepal (Rajarshi Janak University Research Journal, 2025)
This research investigates the ambient background ionizing radiation (BIR) levels of five locations across seven districts within Bagmati Province, Nepal, using a 451P Pressurized Ion Chamber Survey Meter. These locations include the Araniko Highway, Makawanpur Highway, B.P. Highway, Kavrepalanchowk, and Kathmandu Valley. The study aims to evaluate the variations in BIR levels, quantify associated radiological hazard indices, and compare the results with a prior study conducted in 2023 using a RadAlert™ 100 radiation monitor. The acquired measurements reveal an average BIR of (0.016 ± 0.001) mR/hr, which exceeds the global average (0.013 mR/hr) by approximately 1.2 times. This can be primarily attributed to the region's geological composition. The highest BIR level was observed in Kathmandu Valley (0.017 mR/hr), and the lowest one was recorded along the Araniko Highway (0.014 mR/hr). Calculated hazard indices such as equivalent dose rate (EDR), absorbed dose rate (ADR), annual effective dose equivalent (AEDE), and excess lifetime cancer risk (ELCR), suggest that despite the moderately increased BIR levels, there is no significant radiological threat or hazard to the public health. Comparison with the 2023 study highlights the influence of measurement devices on recorded values, with RadAlert™ 100 yielding higher values than the Survey Meter. This study underscores the importance of continuous radiation monitoring for public health safety and provides updated data for radiological assessments in the Bagmati Province.